Bad Samaritans in Foreign Aid: Evidence from Major Mineral Discoveries - Rabah Arezki; Youssouf Camara; Frederick van der Ploeg; Grégoire Rota-Graziosi (CESifo GmbH, 2024)
This paper explores whether foreign aid is self-interested, exploiting the timing and size of major mineral discoveries. We first analyze the effect a resource discovery in a two-by-two donor-recipient model with conflict about natural resources, using a contest success function. We then estimate the effects of major discoveries using a gravity model for a large panel of countries. Our empirical estimates are consistent with the predictions of the theoretical model. Results show that recipient countries that experience major discoveries receive more, not less, bilateral aid, all else equal. Our benchmark result is that following a mineral discovery, a recipient country receives 36% more aid compared to a country without such a discovery. That is a paradox considering that major discoveries are associated with an effective relaxation of international borrowing constraints.
Keywords: E00; F30; O10; O20; 330; bilateral aid; self-interested donors; mineral discoveries; contests